Measurement Performance Improvement of Buried Strain Sensors for Asphalt Pavement Using Mesoscale Finite Element Simulation - Haiyang Hu; Gang He; Man Huang; Dongdong Han; Hongzhou Zhu; Yongli Zhao (Sensors)
Accurately measuring strain in asphalt pavements using buried strain sensors remains challenging due to the temperature sensitivity and heterogeneity of asphalt mixtures. This study focuses on improving the measurement performance of buried strain sensors in asphalt mixtures through finite element simulations. First, the sensing errors of existing buried strain sensors in asphalt mixtures were analyzed based on laboratory experiments. Subsequently, the factors affecting the deformation compatibility between the sensor and the asphalt mixture were investigated, and the effect of asphalt mixture heterogeneity on the stability of the sensor measurements are discussed. More importantly, a series of optimization strategies for buried strain sensors are proposed. The findings suggest that the equivalent modulus of the buried strain sensor should closely match that of the asphalt mixture, and its encapsulation must avoid inducing any reinforcement effects. Considering the dynamic modulus range of the asphalt mixture, it is recommended to adopt the lower bound, such as 0.25 GPa, as the equivalent modulus of the buried sensor. To eliminate the stiffening effect, the encapsulation may utilize low-modulus flexible materials. The inherent heterogeneity of asphalt mixtures influences the measurement stability of buried strain sensors: a higher overall modulus leads to a more uniform internal strain distribution, whereas a larger nominal maximum aggregate size (NMAS) results in poorer strain field uniformity. Increasing the gauge length of the buried strain sensor to at least three times the NMAS significantly enhances measurement stability. This study provides valuable guidance for the design of buried strain sensors in asphalt pavement applications.